(untitled) (REMUNOM, 2024)
This article is linked to a new prospectus on child labor, which is used via the internet, that is, known as child YouTubers. This is a topic that generates a lot of discussion in this new modality. These are children who are gaining a lot of visibility and generating great profit on top of that. In this way, they undertake long and high workloads recording content for digital platforms such as YouTube, and in a way exposing their lives as a digital influencer. This is becoming more and more common in many children who dream of starting to make videos because of their age and completely forget what it’s like to actually be a child and live the right way they should live, as they get too caught up in work relationship and forget to play and have their leisure time. In this way, the way in which this type of work is treated is worrying, as it is artistic children’s work, which can bring many risks to children due to the way they are exposed at such a young age. As a result, in Brazil, in fact, there is no law that guarantees that these “young YouTubers” have well-divided tasks so that it is not a burden for them, so that they have limitations. With regard to this issue, it is to show that this type of work is indeed a form of child labor and that it must be taken seriously in the creation of legislative standards so that the child can leave this digital world and experience the world in a light way.